Wind Energy Conversion Systems: Technology and Trends - Muyeen, S.M. (2012)
In this chapter, first, the global wind power scenario is depicted followed by the market forecasting upto the year 2030. Then the current technology and the future trend of wind energy conversion system are discussed where the development of wind generator, blade designing, lightning protection, installation, commissioning, operation and maintenance of wind turbine generator unit are briefly stated. Some important issues such as variability and predictability of wind power, energy storage option and grid interfacing are discussed as well. Prime offshore wind farm technology issues in terms of feasibility study, bulk power transmission scheme are discussed in detail. Finally, the highlights of all the chapters are given from where the flavor of the book can be obtained at a glance.